Green Banking: The Perspective of Maqãshid Al-Syari’ah - Ansori, Ahmad Insya' (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. Global environmental challenges are driving every sector. Banking must adapt and contribute to achieving sustainable development. Green banking has emerged as an innovative solution that focuses on financial benefits as well as environmental and social responsibility. Aims. Integrating the principles of maqãshid al-Syari̅’ah with the concept of green banking. Method. The literature study uses a qualitative approach with descriptive analysis to better understand the concept of green banking in the context of maqãshid al-Syari̅’ah Result. Green banking not only contributes to environmental preservation but also helps banks build a stronger and more sustainable portfolio. The conclusion of this research emphasizes the importance of applying maqãshid al-Syari̅’ah principles to support the sustainability of the banking sector in the future.